Unemployment and Labor Market Issues in Algeria - Furceri, Davide (IMF Working Papers; Working Paper ;, 2012)
The aim of this paper is to analyze unemployment and labor market developments in Algeria and assess the factors that may hamper employment creation. The results of the paper suggest that the relative low output-employment elasticities and rigid labor market are the main factors behind the still high level of unemployment, particularly among the youth. Simulation analyses, based on the results on the relation between labor market institutions and unemployment, show that improvement in labor market conditions in Algeria would be key in reducing unemployment both in the short- and medium-term.